ANALISIS KUALITAS LAYANAN PENGOLAHAN DATA GAJI GAJI PEGAWAI NEGERI SIPIL STUDI KASUS DI PEMERINTAH KABUPATEN SUKOHARJO - , Haryanti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to determine the influence of customer perceptions of the service of salary data processing of Civil Servants in the Government District of Sukoharjo, based on Service Quality dimensions which are tangible, assurance, reliability, responsiveness and empathy as well as to learn the value of the gap between perceptions and expectations of the customers to service of salary data processing. Subjects are 100 customers salary data processing of the civil government of Sukoharjo. Data are collected by purposive sampling. Data collection was in the period of 18 until 30 October, 2010. The analytical tool used is linear regression with the help of SPSS software. The testing phase begins with the validity and reliability, then testing for normality and hypothesis. The results show that the dimensions of the Service Quality of Tangible, Assurance, Reliability, Responsiveness and Empathy affect customer satisfaction on salary data processing of Civil Servants in the Government District of Sukoharjo. The variables that most influence the customer satisfaction are the tangible variables and the least influential is the assurance variables. The average score of the customer's expectations are higher than average perception score. This may indicate that the quality of the service of salary data processing performed by the Electronic Data Processing Section of Sukoharjo Government has not met customer expectations. This study shows that the variation of customer satisfaction can be explained by variations in dimensions of Service Quality which support by the coefficient of determination of 0,857.